PENGARUH BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI) - Tundjung, Ghafara Mawaridi Mazini; Haryanto, Haryanto (Diponegoro Journal of Accounting, 2015)
This study aims to examine the effect of deferred tax expense on the earningsmanagement case study in manufactured listed companies in Indonesia Stock Exchange. While financial restatement are measured using dummy variable which used “1” if the firm ply earnings management and “0” if the firm ply non-earnings management. This study also tests several control variables namely firm size, leverage, growth.Data for this study are obtained from annual report of companies listed on Indonesia Exchange Stock (BEI) in 2011-2013. Sampling using purposive sampling method, the sample is selected using certain considerations that are tailored to the purpose of research or study problems developed so that the sample in this study amounted to 55 companies in the third period of the study to 1655 companies. The hypothesis testing use logistic regression analysis.The results showed that the Deferred tax expense significant positively affects the earnings management, While discretionary accrual did not significantly affects the Earnings Management